Strategi Guru dalam Implementasi Kurikulum Merdeka pada Pembelajaran Pendidikan Agama Buddha dan Budi Pekerti di Sekolah Dasar Swasta Amitayus - Putra, Desvian Dharma; Sulani, Puji; Sutadi, Sutadi (STAB Kertarajasa, 2025)
This study aims to analyze the strategies employed by teachers in implementing the Merdeka Curriculum in Buddhist Religious Education and Character Education. This research was conducted at SDS Amitayus and used a qualitative approach with a case study method. The research subjects include the principal, a Buddhist Religious Education and Character Education teacher, and two students. Data were collected through interviews, observations, and documentation, then analyzed using data analysis techniques from Miles, Huberman, and Saldaña. The results indicate that the implementation strategy of the Merdeka Curriculum occurs through three stages: preparation, implementation, and evaluation. The preparation stage includes acquiring Knowledge, understanding the Merdeka Curriculum, and designing learning tools. The implementation stage involves the learning process, initial adaptation, and monitoring. The evaluation stage is carried out through formative and technical evaluations. Challenges faced by teachers occur mainly during the preparation and implementation stages, including limitations in learning resources, facilities, and infrastructure, as well as a lack of initial understanding of the Merdeka Curriculum. To overcome these difficulties, teachers rely on Knowledge-seeking, self-directed learning, and modification of teaching modules to address resource constraints.